Evaluation of Ceruloplasmin and Some Biochemical Parameters in Iraqi Patients With Coronary Artery Disease - AL-Fayyadh, Mohanad S. (Iraqi Journal of Science, 2026)
The current work aimed to clarify the various biochemical parameters in individuals with coronary artery disease (CAD) that impact the ceruloplasmin activity. Thus, patients with CAD (n=38 CAD participants) and a healthy control group (n=38) were included. Their ages ranged from 42 to 67 years old. Ceruloplasmin activity (Cp), triglycerides (TG), total cholesterol (TC), high-density lipoprotein (HDL-c) , total protein (TP),   albumin, creatinine, urea, malondialdehyde (MDA), and calcium were measured in the study in serum samples from each group. The findings of the comparison of measured parameters between CAD and control groups were as follows: Results revealed that the levels of TG, TC, VLDL-c, LDL-c, globulin, TP, creatinine, urea, MDA, and ceruloplasmin activity were significantly higher in CAD group compared with controls, whereas albumin, HDL-c, and calcium levels have been significantly lower.